Tunable Self‐Assembly of Triazole‐Linked Porphyrin–Polymer Conjugates. Issue 38 (12th August 2013) - Roberts, Derrick A.; Schmidt, Timothy W.; Crossley, Maxwell J.; Perrier, Sébastien
Abstract The convergence of supramolecular chemistry and polymer science offers many powerful approaches for building functional nanostructures with well‐defined dynamic behaviour. Herein we report the efficient "click" synthesis and self‐assembly of AB2‐ and AB4‐type multitopic porphyrin–polymer conjugates (PPCs). PPCs were prepared using the copper(I)‐catalysed azide–alkyne cycloaddition (CuAAC) reaction, and consisted of linear polystyrene, poly(butyl acrylate), or poly(tert‐butyl acrylate) arms attached to a zinc(II) porphyrin core via triazole linkages. We exploit the presence of the triazole groups obtained from CuAAC coupling to direct the self‐assembly of the PPCs into short oligomers (2–6 units in length) via intermolecular porphyrinatozinc–triazole coordination. By altering the length and grafting density of the polymer arms, we demonstrate that the association constant of the porphyrinatozinc–triazole complex can be systematically tuned over two orders of magnitude. Self‐assembly of the PPCs also resulted in a 6 K increase in the glass transition temperature of the bulk material compared to a non‐assembling PPC. The modular synthesis and tunable self‐assembly of the triazole‐linked PPCs thus represents a powerful supramolecular platform for building functional nanostructured materials.